The Size and Shape Dependence of Ferromagnetism in Nanomagnets. (17th May 2012) - Li, Ying; Li, Yongfeng; Wang, Tianxing
Abstract : The size and shape dependence of dynamic behaviors of nanomagnets is studied by the kinetic Monte Carlo method based on the transition state theory. We analyze the hysteresis curves of the nanomagnet systems with different shapes (or spin array patterns) in the presence of an external magnetic field. The results show that the magnetization of the chain-shaped nanomagnet is more sensitive to the applied field than that of the oblong-shaped or bulk-shaped systems. For the same magnetic nanostructure, the coercive field presents an exponential decay with temperature. Moreover, the coercive field is found to be strongly dependent on the effective coordination number, which has different values corresponding to those systems of different size and shapes (spin array patterns).